Periodontal health in Troms County, Northern Norway. Descriptive, subject level and site-specific analyses - Holde, Gro Eirin (Journal of Periodontology, 2019)
Background/Aim - Periodontal disease is one of the most prevalent diseases in the world. There is a scarcity of epidemiological studies of periodontal disease in Norway. The overall aim of this thesis was to assess the burden of periodontitis in an adult population, and to explore risk factors, as well as health-promoting factors related to the disease. Methods - The thesis is based on a cross-sectional study of an adult population (20-79 years old). Data were collected between October 2013 and November 2014 in Troms County, Northern Norway. Information about sociodemographic characteristics, behavioral factors, oral health-related quality of life, and sense of coherence was collected by self-reported questionnaire. Periodontal probing depth, bleeding on probing and presence of plaque were assessed for all teeth. Radiographic bone loss was examined using orthopantomograms. Results - Half of participants had periodontitis (CDC/AAP case definition), of which 9% had severe periodontitis. Periodontitis prevalence increased markedly with age, was higher among men, and positively associated with smoking, lower levels of education, and lower income. Using Andersen’s behavioral model of health services use, more social structure and stronger SOC was related to enabling resources, which in turn was associated with more use of dental services. More use of dental services was related to more periodontitis and more periodontitis was associated with increased oral health impacts. Gingival bleeding was affected by local, behavioral and socioeconomic factors. Smoking reduced the general bleeding tendency of the gingiva and attenuated the response to supragingival plaque. Conclusions - There is a high burden of periodontitis among adults in Troms County. Socioeconomic factors and smoking were main predictors of periodontitis. Smoking strongly affected the clinical expression of gingivitis. There is a complex relationship between population characteristics, use of dental services and oral health outcomes. Regular dental visiting ...